Prospects for Islamic Economic Development in the Digital Era - Alip Toto Handoko; M. Abdul Aziz; Muhamad Ulul Fahmi (al-Afkar, Journal For Islamic Studies, 2025)
The development of the digital era has compelled all sectors, including Islamic banking, to undergo digitalization. Coupled with the advent of Digital Financial Innovation (DFI), Islamic banks must participate in this transformation to avoid being left behind. Therefore, it is crucial to study the prospects for the future development of the Islamic economy by examining the opportunities and challenges faced by Islamic banks to survive and continue to thrive in the current era of digitalization. The research method in this article is descriptive qualitative. The analysis results indicate that: Islamic Banking as a New Business Model Organizer, Islamic Banking is one of the organizers of a new business model known as "digital financial innovation." This model integrates financial services with the digital ecosystem. Opportunities in the Digitalization Era: The majority Muslim population and effective promotion are opportunities for Islamic banking in the digitalization era. The challenges faced by Islamic banking include human resources, cybersecurity, consumer protection, and low financial literacy in society. Thus, to continue to grow, Islamic banking must be able to overcome these challenges while leveraging the opportunities available in the digital era.